IMPACT OF MEMBER'S DEPOSITS AND MEMBER'S LOANS ON THE REST OF BUSINESS PROFITS ON COOPERATIVE PARTNER MANDIRI, LIRIK DISTRICTS, INDRAGIRI HULU - Suharmiyati Suharmiyati; Yenny Iskandar (LPPM Press STIE Indragiri Rengat, 2021)
The purpose of this study was to gain an understanding of the savings and loan cooperatives as a whole. Apparently savings and loan cooperatives are an important part of the Indonesian economy and can be beneficial for the lives of members. So, this study aims to determine the implementation of savings and loan cooperative procedures from all parties, problems and benefits. Therefore, the main research method is interview. This study shows that the use of savings and loan cooperatives can provide solutions for speed, accuracy and accuracy in carrying out saving and loan data processing in order to get optimal results. So this cooperative was established for member savings, member loans and there will be a distribution of SHU for all members.The Mitra Mandiri Cooperative, Lirik Districts, which is located in the Lirik sub-district, was established in 2012, but since 2012 it has developed until now. The loan process is based on a joint responsibility system and most loans are used for education and additional business capital. Cooperative Mitra Mandiri Lirik Districts strives to empower its members and employees more strongly with regular education and training. Furthermore, there is recreation every year to encourage member approaches and emphasize a family atmosphere.One of the important parts of the Cooperative Mitra Mandiri Lirik Districts is Savings and Loans which has been rolled out until now running smoothly.